Mechanical Evaluation of an Elastomeric Cushion For Total Knee Replacement - Kelly, Brian (My University, 1992)
Mechanical factors have been cited as a primary cause of total knee replacement failure. A hypothesis has been formulated stating that the introduction of a compliant interface into a total knee prosthesis would moderate excessive stresses and strains, thereby, extending joint life. A biocompatable elastomer developed by the Dow Corning Corporation was selected for mechanical evaluation as a cushioning material. Force-strain, impact, and fatigue tests were conducted on several specially designed and fabricated elastomer test shapes. Test results demonstrate that a suitably stiff and dynamically responsive elastomer cushion can be designed to handle repeated physiological knee joint loads. Physiological impacts with cadaver tibias demonstrated significant shock reduction benefits, including peak force reductions of up to 70%, with the addition of different elastomer shapes. Compressive fatigue evaluation of elastomer samples was inconclusive owing to extensive sample wear. As a result configurations or applications where the elastomer can move relative to a rigid surface are not recommended. A new, mechanically contained elastomer shape was designed and tested which greatly reduced wear. Bonding of this new shape to prosthetic joint materials is recommended for further experimental evaluation.
Mechanical Evaluation of an Elastomer Cushion For Total Knee Replacement
Keywords: mechanical; mechanical evaluation; elastomer; elastomeric; elastomeric cushion; total knee replacement; knee; knee replacement; cushion for total knee replacement; elastomeric cushion for total knee replacement; elastomer cushion for total knee replacement; mechanical engineering; engineering